Math Problem Statement

cos(3x+2)sin4(3x+2) dx\int\cos\left(3x+2\right)\sin^4\left(3x+2\right)\text{ dx}

Solution

We are tasked with evaluating the integral:

cos(3x+2)sin4(3x+2)dx\int \cos(3x + 2) \sin^4(3x + 2) \, dx

Step 1: Substitution

Let us start by making the substitution: u=3x+2u = 3x + 2 This gives: du=3dxdx=du3du = 3 \, dx \quad \Rightarrow \quad dx = \frac{du}{3}

Substituting into the integral: cos(u)sin4(u)du3\int \cos(u) \sin^4(u) \frac{du}{3}

Factoring out the constant: 13cos(u)sin4(u)du\frac{1}{3} \int \cos(u) \sin^4(u) \, du

Step 2: Simplifying with Power Reduction

We can express sin4(u)\sin^4(u) using the identity sin2(u)=1cos2(u)\sin^2(u) = 1 - \cos^2(u): sin4(u)=(sin2(u))2=(1cos2(u))2\sin^4(u) = (\sin^2(u))^2 = (1 - \cos^2(u))^2

Expanding (1cos2(u))2(1 - \cos^2(u))^2: sin4(u)=12cos2(u)+cos4(u)\sin^4(u) = 1 - 2\cos^2(u) + \cos^4(u)

Thus, the integral becomes: 13cos(u)(12cos2(u)+cos4(u))du\frac{1}{3} \int \cos(u) \left(1 - 2\cos^2(u) + \cos^4(u)\right) \, du

Step 3: Breaking the Integral into Three Terms

We can now split the integral into three simpler integrals: 13(cos(u)du2cos3(u)du+cos5(u)du)\frac{1}{3} \left( \int \cos(u) \, du - 2 \int \cos^3(u) \, du + \int \cos^5(u) \, du \right)

Integral 1: cos(u)du\int \cos(u) \, du

This is straightforward: cos(u)du=sin(u)\int \cos(u) \, du = \sin(u)

Integral 2: cos3(u)du\int \cos^3(u) \, du

Using the identity cos3(u)=cos(u)(1sin2(u))\cos^3(u) = \cos(u)(1 - \sin^2(u)), we get: cos3(u)du=cos(u)ducos(u)sin2(u)du\int \cos^3(u) \, du = \int \cos(u) \, du - \int \cos(u) \sin^2(u) \, du The first part is sin(u)\sin(u), while the second part requires a substitution. However, this integral follows a known result: cos3(u)du=sin(u)3+sin3(u)3\int \cos^3(u) \, du = \frac{\sin(u)}{3} + \frac{\sin^3(u)}{3}

Integral 3: cos5(u)du\int \cos^5(u) \, du

Similarly, we use the identity cos5(u)=cos(u)(1sin2(u))2\cos^5(u) = \cos(u)(1 - \sin^2(u))^2, and the result for this is: cos5(u)du=sin(u)5+sin3(u)5+sin5(u)5\int \cos^5(u) \, du = \frac{\sin(u)}{5} + \frac{\sin^3(u)}{5} + \frac{\sin^5(u)}{5}

Step 4: Combine Results

Now, combining all the terms, we have:

13(sin(u)2(sin(u)3+sin3(u)3)+(sin(u)5+sin3(u)5+sin5(u)5))\frac{1}{3} \left( \sin(u) - 2 \left( \frac{\sin(u)}{3} + \frac{\sin^3(u)}{3} \right) + \left( \frac{\sin(u)}{5} + \frac{\sin^3(u)}{5} + \frac{\sin^5(u)}{5} \right) \right)

Finally, substitute u=3x+2u = 3x + 2 back into the result.

Would you like me to simplify further or provide details on any of these steps?


Related questions:

  1. How do you solve integrals involving trigonometric identities?
  2. What are common techniques for solving trigonometric integrals?
  3. Can substitution always be applied for integrals like this?
  4. How is the power reduction formula used in integration?
  5. What are the differences between definite and indefinite integrals involving trigonometric functions?

Tip: Use trigonometric identities to simplify complex integrals involving powers of sine and cosine.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Trigonometry
Integration
Substitution
Power Reduction

Formulas

Substitution: u = 3x + 2, du = 3 dx
Power Reduction Identity: \sin^2(u) = 1 - \cos^2(u)
Trigonometric Identities: \cos^3(u) = \cos(u)(1 - \sin^2(u))

Theorems

Trigonometric Integration Techniques
Power Reduction Theorem

Suitable Grade Level

Grades 11-12, College Level Calculus